Sequential Pyridine Dearomatization–Mizoroki–Heck Cyclization for the Construction of Fused (Dihydropyrido)isoindolinone Ring Systems - Joshi, Madhur S.; Pigge, F. Christopher (Synthesis, 2018)
Acylation of 4-alkylpyridines with 2-iodobenzoyl chlorides under basic conditions results in pyridine dearomatization via formation of 4-alkylidene dihydropyridines. These reasonably stable intermediates are further transformed through Pd-catalyzed Mizoroki–Heck cyclization to afford dihydropyrido-fused isoindolinone products in good yield. This study demonstrates successful harnessing of reactive dearomatized pyridine anhydrobases in metal-catalyzed C–C bond-forming reactions, and provides an efficient entry to isoindolinone ring systems structurally related to several indolizidine alkaloid frameworks.
Keywords: dearomatization; Mizoroki–Heck reaction; palladium; isoindolinones; pyridines; alkylidene dihydropyridines; anhydrobases